Inefficiencies on Linking Decisions. - Hortala-Vallve, R (Department of Economics (University of Oxford), 2007)
Jackson and Sonnenschein (2006) show that by linking collective decisions the incentive costs can become negligible and, at the limit, ex-ante e¢ ciency can be achieved. In a voting situation this implies that the agents' intensity of preferences can be taken into account even in the absence of monetary transfers. Rather than considering a limiting result we want to analyse what can be achieved while we consider a …nite number of linked decisions. We fi…rst characterise the set of implementable mechanisms and show that ex-ante efficiency can never be achieved. We then proceed to relax the e¢ ciency requirement and prove that, even when we just require unanimity, the mechanism cannot be sensitive to the agents' intensity of preference.